Sudan : Staff-Monitored Program. (IMF Staff Country Reports; Country Report, 2014)
EXECUTIVE SUMMARY Context: Sudan is a fragile state mired in a heavy debt burden, international sanctions, and volatile domestic and regional political environments. These problems, together with limited revenue mobilization, are constraining Sudan's growth prospects and poverty reduction efforts. The economic situation worsened following the secession of South Sudan in 2011, resulting in the buildup of large economic imbalances. The authorities have embarked on a stabilization program and are expecting that a return of peace in South Sudan will ensure continuation of oil flows, which are crucial for sustaining the government renewed adjustment process resumed last September. Focus of the Staff-Monitored Program (SMP): In the attached Letter of Intent, dated March 7, 2014, the authorities requested a new SMP covering the period January- December, 2014. The objective of the SMP is to restore macroeconomic stability, strengthen social safety nets, and develop the required reforms to refocus the economy on its non- resource sector and lay the groundwork for sustainable economic growth. Risks to the SMP: Risks are mainly tilted to the downside. The social unrest that followed the announcement of the policy measures in September 2013 has abated, but the situation remains fragile. Security conditions remain volatile in several parts of the country, and the current standoff in South Sudan may hinder the flow of oil to Port Sudan. Furthermore, the forthcoming presidential elections in 2015 is already fueling political uncertainty, and complicating the economic policy-making process. Policy recommendations: The main recommendations from the 2013 Article IV consultation were: (i) a fiscal adjustment in the context of the 2014 budget framed in a medium-term strategy, including a gradual phasing-out of fuel subsidies, and a strengthening of social safety nets; (ii) a tighter monetary stance to contain inflation and lessen exchange rate pressures; (iii) further exchange rate flexibility to improve external competitiveness; and (iv) improvement of the business environment to boost private sector- led growth. Debt relief prospects: Relief is predicated on reaching out to creditors, normalizing relations with international financial institutions, and establishing a track record of cooperation with the IMF on policies and payments. Arrears to the Fund: Sudan has been in arrears to the Fund since July 1984. As of end- February 2014, those arrears amounted to SDR 981.5 million.